(untitled) (Al-Mansour Journal, 2022)
Several techniques proposed to retrieve the most relevant HTML documents to user query. Genetic algorithm (GA) one of these technique, which creates several generations iteratively using the operations of: selection, crossover and mutation before producing the results. In this paper, focuses on enhance the operations of GA and proposed new fitness function to enhance the quality of the retrieved results. This technique applied to HTML documents and using recall, precision measures to evaluate. The results show high improvement in the retrieved documents quality in terms of these measures.